The Role of Gut Microbiota in Host Lipid Metabolism: An Eye on Causation and Connection. Issue 7 (19th December 2019) - Wang, Kai; Liang, Xianyi; Pang, Yanli; Jiang, Changtao
Abstract: Lipid‐metabolism‐related disorders are increasingly prevalent and represent growing challenges in terms of prevention and treatment due to their complex and multifactorial pathogenesis. Recently, mounting evidence has suggested that gut microbiota play a crucial role in the regulation of lipid metabolism, which affects the development of lipid‐metabolism‐related disorders. Furthermore, increasingly precise mechanisms underlying the crosstalk between gut microbiota and lipid metabolism have been revealed and may largely deepen the understanding of microbiome. Herein, this paper reviews the relationship between microbiome and host lipid metabolism. First, the correlation between gut microbiota and different lipid metabolism disorders is described. Several causal microbes involved in pathogenesis and disease alleviation are also listed and introduced. Then, the molecular mechanisms involved in microbiome–host crosstalk are briefly discussed. Finally, ceramide, a critical metabolite that connects microbial signals to distal organs, is introduced as the messenger in organ communication. Abstract : This review focuses on the recent progress between microbiome and host lipid metabolism. Four topics including the correlation between gut microbiota and different lipid metabolism disorders, causal microbes involved in pathogenesis and disease alleviation, the molecular mechanisms involved in microbiome–host crosstalk, and ceramide, a critical metabolite that connects microbial signals to distal organs, are elaborately discussed.